STRATEGIES OF CREATIVE MANAGEMENT FOR ADAPTATION OF ORGANIZATIONS IN CONDITIONS OF WAR - BILYK, Victoriia; SHPILEVA, Vira; CHORNYY, Nazarij; KOMPANIIETS, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article provides conceptual characteristics of creative management as a tool that allows for the formation of a set of management solutions, with the help of which it is possible to develop new business ideas and successfully implement them when the external environment of the organization is characterized by an increase in challenges and threats. The need to implement a strategic approach by domestic organizations in establishing creative management is substantiated, the guidelines of which should be considered the development of human capital and the establishment of intellectual and personnel support, which is increasingly difficult to achieve in war conditions. The system of goals and objectives of the strategic policy of creative management, which need to be taken into account by domestic organizations for adaptation to the conditions of war, is defined. A targeted approach to the development and implementation of a creative management strategy for the adaptation of organizations in war conditions consists in creating an optimal personnel development system that ensures the achievement of set goals, guaranteed results and cost minimization, and also takes into account the development of labor resources as a motivating factor. Methods of personnel training as elements of a creative management strategy for adapting organizations in war conditions are summarized. Of course, organizations are not able to face the existing challenges and threats if they do not adhere to the creativity and innovation that embraces creative management. According to this approach, domestic organizations are better able to adapt to external changes, and especially when the economy is in a state of war and the observance of typical methods cannot fully achieve the expected results, and it is necessary to establish procedures for updating and modernizing the management system.
Keywords: creative management; creativity; personnel; strategy; strategic policy; adaptation; organizations; human capital